Intellectual property in the innovation sphere: the Economic and legal aspect - Butnik-Siverskiy, Oleksandr (My University, 2013)
В статті розкривається інститут права інтелектуальної власності, процес трасформації інтелектуальної власності, її стратегія та структура інноваційної моделі розвитку, складові інноваційної діяльності, види інноваційних проектів та маркетинг інновацій, механізм комерціалізації. In the article the author considers intellectual property legal institution, intellectual property transformation process, its strategy and the structure of innovative development model, elements of innovation activity, types of innovation projects and marketing of innovations, commercialization mechanism
Keywords: майнове право; property right; інтелектуальної власності; право інтелектуальної власності; інноваційна діяльність підприємства; innovative activity of the enterprise; комерціалізація інтелектуальної власності; commercialization mechanism